PENANGGULANGAN PEREDARAN MINUMAN KERAS OPLOSAN (Studi Kasus Kecamatan Sirenja Kabupaten Donggala) - Muliadi Muliadi; Imam Basofi Usman (Maleo Law Journal, 2019)
Mixed alcohol is traditional liquor mixed with hazardous ingredients for human consumption because its alcohol content has a level of up to 96 percent, there are several factors that cause people to consume mixed alcohol, including because the price is relatively cheap and easy to obtain. The purpose of this study is to examine the factors that cause the rise of circulation of mixed alcohol in Sirenja District, Donggala District, efforts made to prevent the circulation of mixed alcohol in Sirenja District, Donggala Regency. The long-term goal to be achieved is the realization of the circulation of mixed alcohol in Sirenja District, Donggala Regency. The specific target to be achieved in this research is that the people of Sirenja District can work together in preventing the circulation of mixed alcohol which is very troubling for the community. The research method used in this study is to use the type of normative-empirical research or also called sociological (nondoctrinal) legal research.Keyword: Liquor. Prevention